Clinical and demographic profile of patients with ulcerative colitis at a tertiary care centre, Nepal - Pandey, Rajesh; Prakash Sharma, Rabi (Journal of Chitwan Medical College, 2025)
Introduction: Ulcerative colitis (UC) presents with variable symptoms and disease severity. Its prevalence is rising in Asia, including Nepal. This study aimed to assess clinicodemographics of UC at a tertiary care centre in Nepal. Method: This prospective observational study enrolled all consecutive patients with UC over one year from 01 Jul 2022 to 30 Jun 2023 at gastroenterology department, Civil Service Hospital, Kathmandu, Nepal. Clinicodemographics, presenting symptoms, severity (Truelove and Witts criteria), endoscopic severity (Ulcerative Colitis Endoscopic Index of Severity (UCEIS)), disease extent, and extra-intestinal manifestations were analysed using SPSS 23. Measure of central tendency (mean, median) was used to express numerical data, and distribution for normality was checked. Association between pancolitis and severity of UC were analysed by chi-square; p≤0.05 was considered significant. Result: Sixty-four UC patients, mean age 40.84±14.56 years, had chronic bloody diarrhoea as a common presenting symptom, with 14(21.9%) having extra-intestinal manifestations, mainly polyarthralgia. Although 26(40.60%) had mild disease by Truelove and Witts criteria and 34(53.10%) by UCEIS, most had pancolitis (45.30%). A significant association was found between pancolitis and severe UC on both clinical (p=0.001, ϕ=0.43) and endoscopic assessment (p=0.004, ϕ=0.37). Conclusion: This study reveals a unique UC phenotype with predominant extensive colitis despite mild clinical severity. Significant association of pancolitis with severe disease underscores need for careful assessment beyond symptom severity. Larger population-based studies are essential to gain a more comprehensive understanding of UC in Nepal.